Children and Adolescents during the COVID-19 Pandemic: Analysis of Some Protection Aspects of 10 Latin American and Caribbean Countries - Jesus D.C. Gil; Pedro Manuel Vargues Aguiar (Karger Publishers, 2023)
Background: Latin America has registered cases in children under 14 years of age, which seem few compared to older age groups but are relevant since the child and youth population have been indirectly receiving the most decisive impact of the pandemic. Ensuring the most significant protection for this age group is essential. Methods: This is an ecological study of 10 Latin American and the Caribbean countries to study protecting children and adolescents during the COVID-19 pandemic. Using the information from UNICEF, a coverage analysis was done, and a new variable score was proposed. Also, a multiple linear regression model was tailored to evaluate the relationship between confirmed cases by 100k of COVID-19 (0-14 year population) and the performance of the countries and some key indicators. Results: A strong and statistically significant correlation (r = 0.79; p value 0.005) between the increased coverage of child helplines and a greater number of school closures. Relationship of confirmed cases by COVID-19 and stringency index with a coef B = −2163.6, [CI −3122.1; −1205.1]; p value = 0.010. Cases and healthcare access with a coef B = −17459.7, [CI −25630.1; −9289.5]. Conclusions: Experts say other pandemics will come, and this emergency must be turned into an opportunity. It is vital to strengthen protection programs for the population, especially vulnerable people, such as children and young people. Resumo